Raising of New Chil (Pinus longifolia) Crops - Khan, Fazl Mohammad (Indian Forester, 1943)
Describes various operations under which new chii (P. Longifolia) crops have been raised and conserved in thousands of acres of regeneration areas in chil forests of Murree, Kahuta (Rawalpindi) and Hamirpur (Kangra) hills.